Seasonality and the isotope hydrology of Lochnagar, a Scottish mountain lake: implications for palaeoclimate research - Tyler, J; Leng, M; Arrowsmith, C (2007)
The relationship between isotope ratios in precipitation and lake waters was monitored by bi-weekly measurements taken over a five and a half year period between May 2000 and September 2005 (a period of 1964 days) at Lochnagar, a remote mountain lake in eastern Scotland. Short-term changes in the oxygen isotope composition of lake water (δ18OL) at Lochnagar follow a seasonal pattern similar to isotopes in local precipitation (δ18OP), however changes in catchment residence time, snow accumulation, lake ice cover and lake stratification modify the temporal structure of δ18OL over the seasonal cycle. Of particular importance is precipitation amount, which controls catchment and lake residence times, and determines the degree of phase lag and amplitude change between δ18OL and δ18O P. A simple mass balance model replicates these effects and demonstrates that the degree of phase lag and amplitude reduction is predictable given known input/volume ratio. The implications of these observations for the use of δ18O records in palaeoclimatology are important, since it is rare that authigenic and biogenic minerals or organic compounds (from which δ18O and/or δ2H can be measured) are produced in a lake evenly throughout the year. © 2007 SAGE Publications.